2017
DOI: 10.1200/jco.2017.35.15_suppl.9508
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study of nivolumab or nivolumab combined with ipilimumab in patients (pts) with melanoma brain metastases (mets): The Anti-PD1 Brain Collaboration (ABC).

Abstract: 9508 Background: Nivolumab (nivo) and the combination of nivo + ipilimumab (ipi) improve response rates (RR) and progression-free survival (PFS) compared with ipi alone in clinical trials of metastatic melanoma pts, but pts with untreated brain mets were excluded. Brain mets are a major cause of morbidity and mortality in melanoma and their management is critical. We sought to determine the antitumour activity and safety of nivo and nivo+ipi in pts with active melanoma brain mets (NCT02374242). Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 0 publications
5
61
0
4
Order By: Relevance
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 81%
See 2 more Smart Citations
“…1C). Thus, the outcome of anti-PD-1/anti-CTLA-4 combination therapy was superior to the two monotherapies, which is in line with the reported intracranial response rate for anti-PD-1 monotherapy (21-25%) (12)(13)(14)(15) and anti-PD-1/anti-CTLA-4 combination therapy (50-55%) (15,16), as well as the 6 month progression-free survival rate of 28% and 46%, respectively (15). Due to these promising data, we focused on the anti-PD-1/anti-CTLA-4 combination therapy.…”
Section: The Presence Of Extracranial Tumor Is Critical For Intracransupporting
confidence: 81%
“…A handful of retrospective and prospective clinical studies indicated activity of ipilimumab in melanoma BrM with 16-25% intracranial response rate, but also suggested that only a subgroup of patients is likely to benefit (4,5,11). Pembrolizumab and nivolumab also showed efficacy in melanoma BrM with an ~21% response rate in the brain (12)(13)(14)(15). A very recent interim analyses from two clinical trials in drug-treatment naïve patients with melanoma BrM (ABC trial (15) and CheckMate 204 trial (16)) reported a 50% and 55%…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another nonrandomized clinical trial showed similar results with the combination of nivolumab and ipilimumab in patients with asymptomatic previously treated MBM, that is, an intracranial response of 55% (PFS not reached). These results show that the combination treatment has high activity in asymptomatic patients with MBM …”
Section: Introductionsupporting
confidence: 52%
“…Landmark trials of BRAF inhibitors (BRAFi) and anti-PD-1 checkpoint inhibitor immunotherapy have shown high response rates and prolonged survival in patients with melanoma, but have tended to exclude patients with central nervous system metastasis, particularly those with leptomeningeal metastases (Larkin, Hodi, & Wolchok, 2015;Long et al, 2014;Robert et al, 2015). Subsequent trials in those with parenchymal brain metastases have shown these agents have similar and often concordant responses to extracranial metastasis, but the activity in those with leptomeningeal metastases has not been adequately addressed in any prospective trial (Goldberg et al, 2016;Long et al, 2012Long et al, , 2017Tawbi et al, 2017).…”
Section: Leptomeningeal Melanoma-a Case Series In the Era Of Modern Smentioning
confidence: 99%